Comprehensive review of models and methods used for heat recovery from composting process - Rongfei, Zhao; Wei, Gao; Huiqing, Guo (International Journal of Agricultural and Biological Engineering, 2017)
The large amount of heat produced from solid waste composting has stimulated great interest in heat recovery and utilization. This paper reviews the advances in composting heat recovery researches in the last decade. Some experimental results and theoretical studies on composting heat utilization are summarized. The results indicate a great potential for utilization of heat produced by the composting process. Common problems experienced by current methods are how to realize the maximum heat recovery without negatively impacting compost quality and the economics of heat recovery methods. Further advancement of these methods is currently receiving comprehensive interests, both academically and commercially. Keywords: composting, heat recovery, model and method, heat utilization, solid waste DOI: 10.25165/j.ijabe.20171004.2292 Citation: Zhao R F, Gao W, Guo H Q. Comprehensive review of models and methods used for heat recovery from composting process. Int J Agric & Biol Eng, 2017; 10(4): 1ï¿½12.